(untitled) (Fiep Bulletin - online, 2011)
Systemic Arterial Hypertension (SAH) and renal function are closely related to hypertension may be associated with both a cause and a consequence of chronic kidney disease. In malignant forms or accelerated hypertension may determine a severe renal injury, which may progress with great frequency and little time for a table of end stage renal failure (ESRD). This study was carried out to identify the prevalence of hypertension among patients on hemodialysis in a private practice in Natal / RN. The study is exploratory and descriptive quantitative approach to data obtained from statistical reports generated by the NEFRODATA in relation to the occurrence of hypertension as a factor in the development of CRF in 398 hemodialysis patients enrolled in the system in a nephrology clinic, at Natal/RN, under the Unified Health System (SUS) for the care of patients on Renal Replacement Therapy (SRT). Of the 398 patients, 190 (48%) had hypertension as the underlying disease associated with the development of ESRD, of these 57.9% were male, including age, 40.0% of patients were aged 41 to 60 years and 35 3% were between 61 and 80, with regard to treatment time, we saw that the majority 47.4% were on hemodialysis in the range from 1 year to 5 years and 11 months, followed by those who are less than 1 year of treatment corresponding to 24.2%. Thus we can conclude that hypertension is a chronic disease at high risk for the development of IRC, requiring the promotion, prevention and appropriate treatment of people in basic health units to enable early detection and monitoring disease progression thus preventing renal failure by inadequate control of blood pressure and its complications.